2002
DOI: 10.3758/bf03196796
|View full text |Cite
|
Sign up to set email alerts
|

Time-shrinking, its propagation, and Gestalt principles

Abstract: When a relatively short empty time interval is preceded by an even shorter one, its duration can be underestimated remarkably. This phenomenon, called time-shrinking, has been investigated with patterns consisting of two time intervals. In five experiments, we investigated whether underestimation of the last interval would occur when it was preceded by two time intervals. Significant underestimations of the last interval occurred in some of those patterns. The influence of the second preceding interval was dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Because in our experiment we asked participants to compare crossmodally-defined empty intervals to filled auditory intervals, we have been able to limit the influence of possible biases such as temporal shrinking (Nakajima et al, 1991cited in Nakajima et al, 2004Sasaki et al, 2002), temporal stretching (Sasaki et al, 2010), and temporal ventriloquism effects (Morein-Zamir, 2003). The psychophysical findings on duration perception of crossmodally-defined intervals in our study are overall consistent with previous work (i.e., Grondin & Rousseau, 1991).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Because in our experiment we asked participants to compare crossmodally-defined empty intervals to filled auditory intervals, we have been able to limit the influence of possible biases such as temporal shrinking (Nakajima et al, 1991cited in Nakajima et al, 2004Sasaki et al, 2002), temporal stretching (Sasaki et al, 2010), and temporal ventriloquism effects (Morein-Zamir, 2003). The psychophysical findings on duration perception of crossmodally-defined intervals in our study are overall consistent with previous work (i.e., Grondin & Rousseau, 1991).…”
Section: Discussionsupporting
confidence: 82%
“…If three signals are presented in succession the duration of the interval marked by the second and third signal is underestimated. Sasaki et al (2002) reported that temporal shrinking of the last interval occurs as well when four signals mark three intervals. If we had used two empty intervals in our 2IFC task participants could have interpreted that as a train of four signals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…click train) or events at a faster rate are judged longer than an empty interval or an interval containing less or slower discrete elements, respectively ( Fraisse 1957;Goldstone & Lhamon 1976). Numerous cases of subjective time distortions ('dilation' when objective time is overestimated, 'compression' when it is underestimated) have recently been reported using different paradigms across sensory and motor modalities (Rose & Summers 1995;Yarrow et al 2001Yarrow et al , 2004Hodinott-Hill et al 2002;Sasaki et al 2002;Park et al 2003;Tse et al 2004;Morrone et al 2005;van Wassenhove et al 2008). For example, an oddball within a stream of standard events of identical duration is perceived as longer than a standard event ( Tse et al 2004).…”
Section: Two-way Non-identity Problemmentioning
confidence: 99%
“…In terms of shrinkage, we are reminded of a series of studies by Nakajima and his colleagues on the time shrinking illusion [10][11][12]. It is worth noting that their time shrinking is a completely different phenomenon from our durational shrinkage.…”
Section: Discussionmentioning
confidence: 95%